Ludo Word Game Assisted Visualization Auditory Kinesthetic (VAK) Learning Model on Student Science Learning Outcomes in Elementary Schools - Wiradarma, Kadek; Ketut Gading; I Gusti Ayu Tri Agustiana (MIMBAR PGSD Undiksha, 2023)
The teacher's success in the learning process can be seen from the student learning results. Learning is said to be successful, also seen from how the teacher packages learning. However, teachers are still having difficulties using appropriate learning models in learning. This study aimed to analyze the effect of the Visualization Auditory Kinesthetic (VAK) learning model assisted by the Ludo Word Game. This type of research is a quasi-experimental study with a non-equivalent pretest-posttest control group design. The study population consisted of 45 students, with a random sampling technique to determine the sample. The sample of this research is the experimental class of 23 students and the control class of 22 students. The method used in collecting data is a test. The data collection instrument uses test questions. Data analysis techniques using inferential statistical analysis. The results of the study using the t-test obtained data, namely tcount of 19.893 while for ttable of 2.016, if seen from this, it can be said that tcount is greater than ttable, so there is a significant influence using the Visualization Auditory Kinesthetic (VAK) learning model assisted by Ludo Word Game on science learning outcomes for class V SD. It was concluded that the Ludo Word Game assisted Visualization Auditory Kinesthetic (VAK) learning model improved student learning outcomes. The implication of this research is using the Ludo Word Game-assisted Visualization Auditory Kinesthetic (VAK) learning model to increase students' enthusiasm for learning.